Futures Clinique - method for promoting futures learning and provoking radical futures - Sirkka Heinonen; Juho Ruotsalainen (Springer, 2022)
This paper introduces, illustrates and evaluates the concept of Futures Clinique, which is a participatory and exploratory futures workshop and a collective futures research method to tackle uncertainties, identify disruptions and generate innovations. The Futures Clinique aims at (a) promoting futures thinking, futures preparedness and provocative futures dialogue, and at (b) harnessing collaborative creativity for insights, innovative ideas and practical solutions to the selected futures topics. Examples from certain Futures Cliniques are also presented. Futures Clinique has proved in several exercises to work as a promising tool for collaborative foresight efforts in various organisations. For futures studies, it offers an innovative, visually orientated and structured method for promoting collective futures learning, with a special emphasis on anticipation of surprising futures or Black Swans. A promising solution is to incorporate social media into the concept and use crowdsourcing in the analysis of the mass of ideas collected.